2017
DOI: 10.3390/nu9080829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Biomarkers Associated with Risk of Malnutrition in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Malnutrition is a common yet under-recognized problem in hospitalized patients. The aim of this paper was to systematically review and evaluate malnutrition biomarkers among order adults. Eligible studies were identified through Cochrane, PubMed and the ProQuest Dialog. A meta-regression was performed on concentrations of biomarkers according to malnutrition risks classified by validated nutrition assessment tools. A total of 111 studies were included, representing 52,911 participants (55% female, 72 ± 17 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
238
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(310 citation statements)
references
References 94 publications
18
238
3
9
Order By: Relevance
“…Nevertheless, only approximately 6% of the variability of s-chol could be explained by CRP in the hip fracture patient group. This finding is consistent with a recent systematic meta-analysis of malnutrition biomarkers among older adults that showed that total cholesterol is a useful biomarker of malnutrition in older adults not only in stable non-hospitalized but also hospitalized in acute care settings older adults 25 . Consequently, our findings support the hypothesis that s-chol is a malnutrition indication in hip fracture patients and could be routinely used as part of nutritional assessment in this patient group-taken into consideration that only a small part of its variance is attributed by inflammation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, only approximately 6% of the variability of s-chol could be explained by CRP in the hip fracture patient group. This finding is consistent with a recent systematic meta-analysis of malnutrition biomarkers among older adults that showed that total cholesterol is a useful biomarker of malnutrition in older adults not only in stable non-hospitalized but also hospitalized in acute care settings older adults 25 . Consequently, our findings support the hypothesis that s-chol is a malnutrition indication in hip fracture patients and could be routinely used as part of nutritional assessment in this patient group-taken into consideration that only a small part of its variance is attributed by inflammation.…”
Section: Discussionsupporting
confidence: 92%
“…A simple adoption of the well-accepted BMI cut-off of 18.5 kg/m 2 provided by World Health Organization (WHO) to define malnutrition in hip fracture patients whose mean age is 79 years would likely fail to identify some patients who are at risk of malnutrition. This suggestion is in accordance with a recent meta-analysis aimed at evaluating biomarkers associated with risk of malnutrition in older adults with or without acute illness in general 25 . Previous surveys exhibited that people with hip fracture have significantly lower MAMC and TST than healthy elderly controls which was also apparent in our study 29 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Cutoff values of 24 cm, 27 cm, and 3 cm were used to detect malnutrition with midarm circumference, calf circumference, and triceps skinfold thickness, respectively . Given that blood biomarkers for malnutrition remain widely used in clinical practice, we also included hemoglobin and serum albumin level for nutrition biomarkers in older adults, as suggested by a recent systematic review …”
Section: Methodsmentioning
confidence: 99%
“…Serum albumin level may peak at around 20 years of age in the general population, after which it decreases [33]. Older patients are more likely to suffer from malnutrition, which reduces serum albumin levels [34,35]. Age has also been identified as an independent risk factor for HT in cerebral embolism patients [4].…”
Section: Discussionmentioning
confidence: 99%